Near‐infrared reflectance spectroscopy for forage nutritive value analysis in sub‐Saharan African countries. (6th September 2021) - Balehegn, Mulubrhan; Varijakshapanicker, Padmakumar; Zampaligre, Nouhoun; Blummel, Michael; Ayantunde, Augustine; Jones, Chris; Prasad, Kodukula Venkata Subrahamanya Vara; Duncan, Alan; Dejene, Mesfin; Adesogan, Adegbola T.
Abstract: Limited supply of quality feed is the most common problem limiting livestock productivity in sub‐Saharan Africa (SSA). Routine feed evaluation is indispensable for formulating balanced rations, feed characterization, safety, and minimizing the environmental impact of livestock. Traditional wet chemistry has not met this demand in SSA because it is time consuming, expensive, reliant on imported reagents and equipment that requires regular maintenance. Near infrared reflectance spectroscopy (NIRS) is a rapid and accurate alternative. The NIRS can help meet the need to characterize locally available forages and feeds on the continent, thus allowing formulation of optimally balanced and safe rations, facilitating establishment of nutritive value‐based pricing, and improving feed marketing and environmental stewardship. Though several NIRS systems have been purchased in many SSA countries, few are currently used. Reasons include high upfront costs, lack of requisite technical capacity, lack of access to comprehensive wet chemistry‐based databases to develop and validate robust and accurate predictive equations, lack of access to or relevance of existing validated equations, and limited awareness about the value of NIRS. Recently developed portable devices can dramatically reduce cost, while providing flexibility and comparable accuracy to benchtop systems. Formation of NIRS consortia and communities of practice including public–private partnerships that link equipment, pool resources, and provide periodic training and troubleshooting, can address many of these problems. This paper elaborates the potential for using NIRS to improve feed analysis in SSA countries, the reasons for the low use of existing systems, and strategies to improve the adoption and use of NIRS. Core Ideas: Forage nutritive value analysis is crucial for solving feed problem in sub‐Saharan Africa (SSA). Wet chemistry is expensive, time consuming, and dependent on reagents, limiting its use in SSA. Near infrared reflectance spectroscopy (NIRS) provides a quick, flexible and accurate alternative. NIRS use in SSA is limited by limited knowledge, cost, lab resources, and calibration equations for local feeds. Low‐cost, portable NIRS brands and regional NIRS consortia can solve resource limitations.